2002
DOI: 10.1128/jvi.76.11.5557-5564.2002
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Phage Replication Threshold: a Mathematical Model with Implications for Phage Therapy

Abstract: Prior observations of phage-host systems in vitro have led to the conclusion that susceptible host cell populations must reach a critical density before phage replication can occur. Such a replication threshold density would have broad implications for the therapeutic use of phage. In this report, we demonstrate experimentally that no such replication threshold exists and explain the previous data used to support the existence of the threshold in terms of a classical model of the kinetics of colloidal particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 14 publications
(12 reference statements)
8
163
0
2
Order By: Relevance
“…3B) could result from reduced endotoxin release. Based on a statistical analysis, it has been suggested that delivery of bactericidal agents by nonreplicating phage may represent a viable antimicrobial strategy (13). In fact, lethal agents delivered by a filamentous M13 phage variant have been shown to reduce the level of E. coli cells in the blood of mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…3B) could result from reduced endotoxin release. Based on a statistical analysis, it has been suggested that delivery of bactericidal agents by nonreplicating phage may represent a viable antimicrobial strategy (13). In fact, lethal agents delivered by a filamentous M13 phage variant have been shown to reduce the level of E. coli cells in the blood of mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…In Streptococcus thermophilus, Cas9 is constitutively produced and it confers a fitness cost that is most pronounced during lag phase and at low cell density, when the risk of phage infection is low (7,13,19). Experiments show that CRISPR-Cas-mediated autoimmunity results in deleterious effects, ranging from genome rearrangements and cell filamentation to suicide (9).…”
Section: Significancementioning
confidence: 99%
“…CRISPR-cas is repressed by glucose and activated by cAMP receptor protein-cAMP in Pectobacterium atrosepticum (17). In addition to these mechanisms, theory and data suggest phage proliferation-and therefore risk of infectionincreases with increasing bacterial cell density (18,19). Bacteria monitor cell density using a cell-cell communication mechanism known as quorum sensing (QS).…”
mentioning
confidence: 99%
“…This was again supported by studies on the control of spoilage bacteria on meat surfaces, which suggest that phages can be effective biocontrol agents when the population of host cells is as low as 46 CFU/cm 2 (Greer 1988). Hence, the requirement of a minimum bacterial density as a prerequisite for successful phage biocontrol was not accepted (Kasman et al 2002).…”
Section: Influence Of Phage and Host Concentration On Biocontrolmentioning
confidence: 86%